Boundary limit for commercial productivity of vinca rosea - Izzat Shaharuddin (School of Bioprocess Engineering, University Malaysia Perlis, 2011)
The objectives of this project are to evaluate factors that affect commercial productivity, postulate the upper and lower boundary limit and to analyze limitation factor that need to considered in production of vinblastine. The investigation is divided into 3 major section area; planting, extraction and scale-up. In planting study, the productivity of vinca rosea and harvest frequency for 1 hectare field is determined. Study show that 2.0 tons/hectare of vinca rosea leaf can be obtained every 3 months. The extraction study is to identify how much product can be obtained from a chosen method. Dry vinca rosea leaf can produced 0.0145% of final product. Finally, the scale-up section is done to determine commercial productivity through simulation that by excel based on the convection data from experiment and investigate study. The study show that, 1.0 g vinblastine production need 46 m2 to 71 m2 field area to plant vinca rosea. Based on simulation study, other production such as machine, time, material, man power and process method use in production must be also considered since it will affect productivity process.